2014
DOI: 10.1210/en.2013-1928
|View full text |Cite
|
Sign up to set email alerts
|

Novel Vasotocin-Regulated Aquaporins Expressed in the Ventral Skin of Semiaquatic Anuran Amphibians: Evolution of Cutaneous Water-Absorbing Mechanisms

Abstract: Until now, it was believed that only one form of arginine vasotocin (AVT)-regulated aquaporin (AQP) existed to control water absorption from the ventral skin of semiaquatic anuran amphibians, eg, AQP-rj3(a) in Rana japonica. In the present study, we have identified a novel form of ventral skin-type AQP, AQP-rj3b, in R. japonica by cDNA cloning. The oocyte swelling assay confirmed that AQP-rj3b can facilitate water permeability. Both AQP-rj3a and AQP-rj3b were expressed abundantly in the ventral hindlimb skin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…4 ). This suggested that a cAMP-dependent phosphorylation mechanism may be involved in the trafficking of the Glp_v1 channel to the plasma membrane as reported for some vertebrate [ 10 , 12 , 70 74 ] and plant aquaporins [ 75 77 ]. An in silico analysis of the putative phosphorylation sites indicates that five residues in the N-terminus of Glp1_v1 (Ser 2 , Thr 3 , Tyr 9 , Thr 14 and Ser 21 ) differ in phosphorylation potential compared to the Glp1_v2 isoform (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…4 ). This suggested that a cAMP-dependent phosphorylation mechanism may be involved in the trafficking of the Glp_v1 channel to the plasma membrane as reported for some vertebrate [ 10 , 12 , 70 74 ] and plant aquaporins [ 75 77 ]. An in silico analysis of the putative phosphorylation sites indicates that five residues in the N-terminus of Glp1_v1 (Ser 2 , Thr 3 , Tyr 9 , Thr 14 and Ser 21 ) differ in phosphorylation potential compared to the Glp1_v2 isoform (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…Cloudsley-Thompson, 1967;Claussen, 1969;Tracy, 1976). Although uncertain, we suspect that some of the physiological parameters affecting skin permeability respond differently to combined changes in temperature and hydration state, possibly involving adjustments in local microcirculatory perfusion of the pelvic patch (Slivkoff and Warburton, 2001;Viborg and Rosenkilde, 2004;Viborg et al, 2006) and constitutive changes in this region's water permeability (Willumsen et al, 2007), mediated by changes in the expression of aquaporins (Hasegawa et al, 2003;Suzuki et al, 2007;Saitoh et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Little is known in the literature to explain the mode of action of propranolol to avoid H 2 O 2 release. It has been shown that, in the skin of frog, propranolol is able to decrease water permeability induced by arginine vasotocin (AVT) (Ogushi et al, 2010; Saitoh et al, 2014). In this model, aquaporins are translocated at the membrane in response to AVT.…”
Section: Discussionmentioning
confidence: 99%